Direct ink writing 3D printing of smart responsive materials - Seah, Matthew Qi Hua (Nanyang Technological University, 2024)
The integration of smart responsive materials into advanced manufacturing processes has emerged as a transformative approach to developing adaptive and multifunctional systems. This study investigates the application of Direct Ink Writing (DIW) 3D printing technology for the additive manufacturing of smart responsive materials capable of detecting and responding to mechanical deformation. Using a 3D printer (Ultimaker) and Conductive PLA filament, a mesh-like structure was fabricated to act as a parallel circuit. The designed structure exhibits dynamic changes in electrical resistance when exposed to stretching deformation, enabling precise detection and measurement of strain in hidden or inaccessible locations. To optimize performance, the study explored the relationship between the printed material's geometry, electrical conductivity, and mechanical deformation, focusing on ensuring reliable signal transmission and repeatability under varying load conditions. The mesh-like design provides a scalable solution for embedding intelligent sensors into complex surfaces or structures without compromising functionality. The findings of this research underscore the versatility of DIW 3D printing in producing advanced smart materials for real-time monitoring applications. Potential applications include structural health monitoring, where deformation detection is critical, wearable devices that track body movements, and adaptive systems that require on-the-fly response to environmental stimuli. This work demonstrates the promise of combining additive manufacturing with conductive materials to pave the way for the next generation of responsive and interactive technologies.